Evaluation of Educational Content Sharing Solutions: Challenges of the mEducator Best Practice Network - Nicolaidou, Iolie; Giordano, Daniela; Spampinato, Concetto; Pattichis, Constantinos S.; Bamidis, Panagiotis; Antoniades, Athos (My University, 2011)
The Best Practice Network (BPN) for medical education (mEducator) aims at implementing and critically evaluating existing standards and reference models in order to address a lack of standardized mechanisms for medical educational content sharing. As part of this work two solutions will be implemented to provide platforms for discovering, sharing, retrieving, repurposing and re-using medical educational content. There is currently no standardized way of evaluating these solutions; however there are other systems and Web2.0 platforms that have commonalities with the mEducator solutions and as such can share aspects of their evaluation approaches. This study reviews the literature to critically compare these approaches, identify points of convergence of their evaluation requirements with mEducator and propose a blueprint for the development of an evaluation framework for assessing the effectiveness of the platforms that will be implemented through the mEducator BPN and any future platforms that attempt to address the same issues.